Notch y su posible relación con la vía de señalización mediada por TGF-B en el proceso de remielización en el sistema nervioso central - Gómez Pinto, Laura Ivonne (2018)
Adult neural progenitor cells (aNPCs) can differentiate into both neurons and glial cells such as astrocytes and oligodendrocytes throughout life. The Notch signaling pathway and transforming growth factor ?1 (TGF-?) are known to play critical roles in cell fate decisions. TGF-? has been previously shown to exert pro-neurogenic effects on the NPCs present in the hippocampal and subventricular zones (SVZ) and to interact with Notch signaling in different cell types. For this reason, the goal of this work was to study the effect of TGF-? on the commitment of NPCs of the SVZ to a glial fate and its interaction with the Notch signaling pathway.\nInitial cell characterization of NPCs from the SVZ revealed a large percentage of Olig2+, Nestin+ and GFAP+ cell populations, while a small percentage of PDGFR?+ and NG2+ and less than 1% TujI+ cells. Immunocytochemical analysis showed a significant increase in the percentage of PDGFR?+, NG2+ and GFAP+ cells during treatment with TGF-? for 4 days, which is consistent with the increase observed in PDGFR?+ cell proliferation after 24-hour treatment with TGF-?. These results demonstrate the pro-gliogenic effect of this cytokine on the population of NPCs from the adult SVZ. Real-time polymerase chain reaction (PCR) analysis showed TGF-? to induce the expression of Notch ligand and Notch pathway activation target gene Hes1. These findings demonstrate the involvement of Notch signaling in the effects of TGF-?. The characterization of cultures subjected to treatment with TGF-? for 8 days revealed a still high proportion of PDGFR?+ cells and an increase in MBP+ cells. Altogether, the results obtained illustrate the impact of TGF-? on cell fate decisions of NPCs from the SVZ toward a glial cell type, as well as on the proliferation and maturation of oligodendrocyte precursor cells (OPCs).